Who Is the Church? An Ecclesiology for the Twenty-First Century : An Ecclesiology for the Twenty-First Century - Peterson, Cheryl M. (Book collections on Project MUSE., 2013)
Many congregations today focus on strategy and purpose--what churches "do"--but Cheryl Peterson submits that mainline churches need to focus instead on "what" or "who" they are--to reclaim a theological, rather than sociological, understanding of themselves. Peterson suggests that we understand the church as a people created by the Spirit to be a community, and that we must claim a narrative method to explore the church's identity--specifically, the story of the church's origin in the Acts of the Apostles. Finally, here is a way of thinking of church that reconciles the best of competing models of church for the future of mainline Protestant theology.